A magnetic massive star has experienced a stellar merger - Frost, Abigail; Sana, H.; Mahy, L.; Wade, G.; Barron, J.; Le Bouquin, J.-B.; Mérand, A.; Schneider, Fabian; Shenar, T.; Barbá, R. H.; Bowman, D. M.; Fabry, M.; et al. (Science, 2024)
Massive stars (those ≥8 solar masses at formation) have radiative envelopes that cannot sustain a dynamo, the mechanism that produces magnetic fields in lower-mass stars. Despite this, approximately 7% of massive stars have observed magnetic fields, the origin of which is debated. We used multi-epoch interferometric and spectroscopic observations to characterize HD 148937, a binary system of two massive stars. We found that only one star is magnetic and that it appears younger than its companion. The system properties and a surrounding bipolar nebula can be reproduced with a model in which two stars merged (in a previous triple system) to produce the magnetic massive star. Our results provide observational evidence that magnetic fields form in at least some massive stars through stellar mergers.
Gesehen am 25.02.2025